Effect of dual optical pulse scheme with supra and subthreshold fluences on laser micro ablation of pigment - Jiho Lee; Hwarang Shin; Seondeok Seo; Jongman Choi; Myungji Kang; Yeachan Lee; Myunggi Yi; Seung Pyo Gong; Hyun Wook Kang (Scientific Reports)
Abstract Q-switched Nd: YAG laser has been widely employed to treat deeply located pigmented lesions by confining the incident laser energy to a target. Currently, a dual pulse mode has been developed to overcome several of the adverse effects, such as irritation and hyper- or hypo-pigmentation. Therefore, the current study investigated the effect of the dual-optical-pulse scheme with an energy distribution ratio of 8:2 (D8:2) on laser micro-ablation of pigment, compared to single pulse and the dual pulses with the equivalent energies. Morphological analysis demonstrated that D8:2 significantly induced the reduction in both number and area fraction of melanophores. Histological analysis revealed that D8:2 decreased the area fraction of the melanophores with minimal laser-induced thermal damage. According to qPCR analysis, the D8:2 group showed the downregulated expression level of SOX10, MITFa, TYR, TYRP1b, and DCT, related to melanin synthesis, and upregulated the expression level of TNF-α, associated with inflammation. Therefore, the current study demonstrated that the dual pulses with an energy distribution ratio of 8:2 could enhance ablation efficacy of the pigment treatment with minimal thermal damage to the adjacent tissue. Further studies will be conducted to investigate the performance of the current findings with various parameters, such as number of pulses and laser irradiation, treatment frequency, and various energy levels.